Low-dose aspirin protects unexplained recurrent spontaneous abortion via downregulation of HMGB1 inflammation activation - Xu, Xiaofeng; Wang, Jing; Zhu, Damin; Yin, Jiaqian; Liu, Jinxian; Wu, Xiao; Yang, Wenjuan; Hu, Qian; Ren, Yu; Zhang, Zhiguo; Zhou, Ping; Wei, Zhaolian; et al. (Frontiers in Endocrinology, 2022)
Background: HMGB1 is considered a kind of sterile inflammatory mediators, which overexpression in patients with URSA. Aspirin as the novel drug target has been revealed. Our previous studies have explored the application of HMGB1 as a therapeutic target of aspirin in URSA disease of mice model and human, but the dynamic process of aspirin down regulating HMGB1 concentration has not been demonstrated. Methods: From December 2018 to November 2020, women with URSA (n=91) and control women (n=90) with no history of recurrent abortion or adverse pregnancy were included in the Reproductive Medicine Center of the First Affiliated Hospital of Anhui Medical University. ELISA was applied to detect the concentrations of HMGB1 and IFN-γ in the peripheral blood. 31 URSA patients were monitored for aspirin treatment (2 and 4 weeks), the changes of HMGB1 and IFN-γ concentrations in peripheral blood of URSA patients before and after using aspirin were compared, and pregnancy outcomes after aspirin treatment were followed up. Results: The levels of HMGB1 in peripheral blood were significantly higher in URSA patients compared with controls, decreasing trends of HMGB1 and IFN-γ concentrations in plasma of URSA patients were observed after treatment with aspirin continuously, the expression of HMGB1 was positively correlated with IFN-γ. There were no birth abnormalities in the babies of the URSA patients treated with aspirin. Conclusions: High levels of HMGB1 may be one of the pathogenesis of URSA. Aspirin may provide protective effect on the HMGB1-triggered URSA.